Optimum fertilizer nitrogen dose for wheat (Triticum aestivum) varieties under rice (Oryza sativa)-wheat cropping sequence - MEHLA, D S; GUPTA, A P (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-93 to find out the optimum fertilizer dose for some promising wheat (Triticum aestivum L. emend. Fiori & Paol.) varieties under rice (Oryza sativa L.)-wheat cropping sequence. The results indicated that the fertilizer N dose for ’WH 542’ and ’HD 2329’ wheat varieties need to be raised to 200 kg N/ha to harvest their potentials. The optimum fertilizer dose for ’WH 533’ wheat was found to be 160 kg N/ha. The performance of ’WH 533’ wheat was better than ’WH 542’ and ’HD 2329’ up to 90 kg N/ha and beyond it ’WH 542’ yielded more, followed by ’HD 2329’ under rice-wheat cropping sequence. Various yield attributes of all the wheat varieties improved with the application of N.